Divergência genética e relações lineares entre produtividade de grãos e caracteres de pendão de milho - Silveira, Daniela Lixinski (2019)
The objectives of this study were to verify genetic variability among maize cultivars in relation to grain yield and tassel traits, to indicate cultivars with divergent characteristics, as well as to study the linear relationships between grain yield and tassel traits and identify which traits have high correlation and direct effects on grain yield. Three experiments were carried out with 20 maize cultivars, in a randomized complete block design, with three replications, in the agricultural years 2015/2016, 2016/2017, and 2017/2018. Were evaluated the 11 traits of tassel and grain yield. The analyzes individual and joint variance were performed. The mean values of the cultivars were compared using the Scott-Knott test. The principal components were analyzed, and with the traits that explained the greatest total variation were determined the Mahalanobis generalized distance matrix between the cultivars and ful filled the analysis of genetic divergence was carried out, using the UPGMA grouping method. To validate the cluster the cophenetic correlation coefficient was calculated. For the study of linear relations, were estimated the matrices of phenotypic and genotypic correlation (by experiment and joint) and the multicollinearity diagnoses were performed, based on the condition number and on the variance inflation factor. After that, the grain yield (main trait) path analysis was performed according to the traits tassel (explanatory traits). There is genetic divergence among maize cultivars and six groups cultivars were formed. Tassel length, total number of branches, dry matter of the central spike and grain yield were the main contributors to genetic divergence among maize cultivars. The number of secondary branches presents a positive linear relation on grain yield and can be used for indirect selection of maize plants in breeding programs.